METHOD OF CALCULATION OF DETERMINING PARAMETERS OF INDIRECT MEASUREMENT FOR SYSTEM OF DIAGNOSIS OF TECHNICAL CONDITION OF PLANTING PLANT SYSTEMS - Масловський, Б. Г.; Зеленков, О. А. (Proceedings of National Aviation University (archive), 2021)
The necessity of determining the diagnostic parameters of indirect measurement of the system of technical diagnostics of the state of automatic landing systems at the stage of operation is substantiated. Methods of calculation of these parameters and determination of their total measurement errors are given.